Предмет: Математика,
автор: focusnik2
sin^4a+sin^2acos^2a-sin^2
Задание
Упростить выражение
Ответы
Автор ответа:
0
Sin^4a+sin^2acos^2a-sin^2
Выносим sin^2l(sin^2l+1*cos^2l-1)=sin^2l(sin^l+cos^l-1)=sin^2l(1-1=0)=sin^2l*0=0
Выносим sin^2l(sin^2l+1*cos^2l-1)=sin^2l(sin^l+cos^l-1)=sin^2l(1-1=0)=sin^2l*0=0
Похожие вопросы
Предмет: История,
автор: Vetta2461
Предмет: Геометрия,
автор: Vov4ik2008
Предмет: Алгебра,
автор: EvgeshaSmirnov
Предмет: Обществознание,
автор: pelmeshkaaa
Предмет: Биология,
автор: Аноним